2019
DOI: 10.3390/v11040342
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Norovirus Outbreaks Reported to the Public Health Emergency Event Surveillance System, China, 2014–2017

Abstract: We conducted a retrospective analysis of norovirus outbreaks reported to the National Public Health Emergency Event Surveillance System (PHEESS) in China from January 1, 2014 to December 31, 2017. We reviewed all acute gastroenteritis outbreaks (n = 692) submitted to PHEESS to identify the frequency, seasonality, geographic distribution, setting, and transmission mode of outbreaks due to norovirus. A total of 616 norovirus outbreaks resulting in 30,848 cases were reported. Among these outbreaks, 571 (93%) occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 36 publications
9
54
0
Order By: Relevance
“…Hospital-based prospective, community-based retrospective and population-based prospective AGE surveillance found that the incidence of NoVAGE decreased with age from 3 to 24 years. The majority (~80%) of NoVs outbreaks reported to the Chinese Public Health Emergency Event Surveillance System (PHEESS) occurred in older children attending kindergartens, primary schools, and secondary schools [20]. The character of the immunity acquired after NoVs infections remains incompletely understood.…”
Section: Population At Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital-based prospective, community-based retrospective and population-based prospective AGE surveillance found that the incidence of NoVAGE decreased with age from 3 to 24 years. The majority (~80%) of NoVs outbreaks reported to the Chinese Public Health Emergency Event Surveillance System (PHEESS) occurred in older children attending kindergartens, primary schools, and secondary schools [20]. The character of the immunity acquired after NoVs infections remains incompletely understood.…”
Section: Population At Riskmentioning
confidence: 99%
“…The incidence of NoVs infection is remarkably low in the Qinghai-Tibet Plateau located in south-west of China [19], probably related to the low humidity in the region. Similar to sporadic NoV AGE, the majority of outbreaks have occurred in the colder season [8,19,20,23,35].…”
Section: Seasonalitymentioning
confidence: 99%
“…Since 2004, provincial and local Centers for Disease Control and Prevention (CDCs) in China have been required to report all acute gastroenteritis outbreaks of >20 cases, including those caused by noroviruses, to a passive national outbreak surveillance system called Public Health Emergency Event Surveillance System (PHEESS) (12). Although PHEESS provides useful information, detailed epidemiologic and molecular data from norovirus outbreaks are typically not included.…”
mentioning
confidence: 99%
“…GI and GII noroviruses are the most important viral cause of non-bacterial gastroenteritis in humans globally. A large proportion of the population is infected with noroviruses via contact with contaminated food, water, and environment every year [17,18,26] 13[P13] genotypes are still evolving and spreading at a lower rate. Although these genotypes might infect humans only sporadically, it is still useful to study the genetic diversity of these norovirus genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high frequency of genetic recombination at the ORF1 and ORF2 junction, a number of recombinant strains have emerged under natural selection [1,17,18]. The emerging virus can replace the old ones and cause new infections and outbreaks every two to four years, as has been observed with GII.…”
Section: Introductionmentioning
confidence: 99%